Comparação morfofuncional entre a espermatogênese e a biologia espermatogonial de dois primatas: homem e sagui - André Lucas Caldeira Brant de Oliveira (2017)
Scientific studies that evaluate testicular function in human under healthy, pathological or experimental conditions often use rodents as experimental models to verify the effects of those conditions on the human testis. Currently, the New World monkeys, especially the genus Callithrix sp, have been widely used in biomedical researches to evaluate testicular biology as a preliminary test in non-human primates. However, despite being phylogeneticaly related to humans, no studies have confidently described if the spermatogenic process between these two species are comparable. Having said that, the objective of the present study was to compare the spermatogenesis morphological and functional parameters’ between the human and the marmoset to further determine if such species could be an adequate experimental model. To do so, testicular samples from four men and five marmosets were processed according to high resolution light microscopy protocols. After the adaptation of the marmoset seminiferous epithelium cycle from nine to six stages, it was observed that, despite having an additional spermatogonial generation, the morphology of marmoset spermatogonia was similar to the human’s ones. In terms of the spermatogenic process, it was observed that the cellular associations present in the six stages of the SEC, their frequencies and one of the spermatogenesis index (meiotic) were similar between both primates’ species. In addition, it was noticed that Adark undifferentiated spermatogonia from both species presented two subtypes: one with nuclear vacuole and another without such structure. Those Adark with a nuclear vacuole were positioned in specific regions nearby blood vessels, suggesting for the first time the presence of a spermatogonial niche in humans. The few morphometric parameters that differed between man and marmoset were due to the different number of spermatogonial generations (Adark, Apale and B in man; and Adark, Apale, B1 and B2 in the marmoset), which does not prevent the comparison between both species. Considering the similarity between the spermatogenesis and spermatogonial biology of both primates, we demonstrated that the marmoset can be used as a more adequate experimental model in studies that aimed to understand the human testicular biology.